2017
DOI: 10.1016/j.optmat.2017.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent properties and energy level structure of CaZnOS:Eu 2+

Abstract: In this work it is shown that CaZnOS:Eu 2+ has no Eu 2+ emission even at low temperature. The observed and earlier reported red emission originates from a CaS:Eu 2+ impurity phase. By means of washing the as-prepared samples with diluted nitride acid, we are able to remove the CaS impurity and get the pure CaZnOS. A clear relation was found between the red emission intensity, the CaS XRD line intensities and the nitric acid solution washing time, with zero intensity after prolonged washing. Later, a so-called … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Just as little Eu 2+ penetrates the cladding layer, CaZnOS:Eu 2+ also has no luminescence because the Eu 2+ 5d states are in the conduction band. 44 As the concentration of Cu + doped on the shell increases, the excitation and emission peaks show a redshift (as in Fig. 3(e) and (f)).…”
Section: Resultsmentioning
confidence: 75%
“…Just as little Eu 2+ penetrates the cladding layer, CaZnOS:Eu 2+ also has no luminescence because the Eu 2+ 5d states are in the conduction band. 44 As the concentration of Cu + doped on the shell increases, the excitation and emission peaks show a redshift (as in Fig. 3(e) and (f)).…”
Section: Resultsmentioning
confidence: 75%
“…It is necessary to explain that due to the mechanism of inward erosion growth, some Eu 2+ also migrates from the CaS:Eu 2+ core to the CaZnOS shell during the synthesis process, but CaZnOS:Eu 2+ does not lead to any luminescence. 45 On the other hand, a small amount of Pb 2+ may enter the CaS core lattice forming CaS:Eu 2+ ,Pb 2+ . It has been reported that energy transfer from Pb 2+ to Eu 2+ occurs in the CaS:Eu 2+ ,Pb 2+ phosphor, resulting in enhancement of the Eu 2+ red emission.…”
Section: Resultsmentioning
confidence: 99%
“…However, the emission of Sm 3+ , Eu 3+ , and Yb 3+ ions was quenched in the presence of the Cu + dopant, probably due to the charge transfer mechanism as judged by the high tendency of these ions to accept electrons (Figure S12, Supporting Information). [ 24 ]…”
Section: Resultsmentioning
confidence: 99%